Financial Performance Analysis at PT. Garuda Indonesia, Tbk - Hastuti Hastuti; Rajindra Rajindra; Guasmin Guasmin (Universitas Muhammadiyah Palu, 2021)
Looking at the formulation of the research problem, the objectives of this study are: (1) To find out and analyze the financial performance of PT. Garuda Indonesia, Tbk when viewed from the liquidity ratio, (2) To determine and analyze the financial performance of PT. Garuda Indonesia, Tbk when viewed from the solvency ratio, and (3) To find out and analyze the financial performance of PT. Garuda Indonesia, Tbk when viewed from the ratio of profitability. This type of research is descriptive research, namely research that describes the financial performance of PT. Garuda Indonesia, Tbk using financial ratio analysis consisting of liquidity ratios, solvency ratios, and profitability ratios as the basis for assessing financial performance or the level of the financial soundness of PT. Garuda Indonesia, Tbk. The data used in this study is secondary data sourced from PT. Garuda Indonesia, Tbk, namely the financial statements of PT. Garuda Indonesia, Tbk (balance sheet, income statement, and cash flow) for the last 5 (five) years. The results showed that: The financial performance of PT. Garuda Indonesia, Tbk. when viewed from the liquidity ratio during the 2014-2018 period, it is in the unhealthy assessment criteria (BBB). Financial performance of PT. Garuda Indonesia, Tbk. when viewed from the solvency ratio during the period 2014-2018 it is in a healthy assessment criterion (A). Financial performance of PT. Garuda Indonesia, Tbk. when viewed from the profitability ratios during the period 2014-2018 it is in an unhealthy assessment criterion (C).